Phytogeographical origin determines Tropical Montane Cloud Forest hydraulic trait composition - Barros, Fernanda de V.; Bittencourt, Paulo L.; Eller, Cleiton B.; Signori‐Müller, Caroline; Meireles, Leonardo D.; Oliveira, Rafael S. (Functional ecology, 2022)
Tropical montane cloud forests (TMCF) have unique climatic conditions, which allow the coexistence of plant lineages with different phytogeographical origins from tropical versus temperate climates. Future climate projections suggest TMCFs will be subjected to increasing drought stress due to fog uplift and higher temperatures, possibly leading to tree mortality and local extinctions, and consequently changes in forest composition and functioning. Characterizing community functional composition, trade‐offs among traits and the drivers of community assembly is of utmost importance to improve our capacity to predict the response of montane plant communities to forecast climate change. Here, we aimed to test whether species from different phytogeographical origins (i.e. tropical – evergreen × deciduous − and temperate) differ in drought vulnerability and how the coexistence of these groups change the hydraulic composition of TMCFs. We used a framework based on measurements of key hydraulic traits (i.e. xylem embolism resistance, hydraulic safety margin, stomata control, turgor loss point, minimum water potential) of 16 dominant species (>70% of the forest basal area) within a TMCF in the Atlantic Rain Forest Domain in southeast Brazil. We used community‐weighted means to model whether removing each species group would change the community hydraulic functional composition. Temperate, tropical deciduous and tropical evergreen groups differ in their hydraulic functioning and these differences explain forest functional composition and taxa dominance. Temperate and tropical deciduous taxa were consistently more vulnerable hydraulically (i.e. lower safety margins and embolism resistance). The coexistence of different phytogeographical lineages is a key determinant of TMCF hydraulic composition. We also used models including phylogeny to evaluate the variation of hydraulic traits across phytogeographical groups, and the results suggest some niche conservatism associated with plant hydraulic functioning. Our results provide evidence of the importance of species phytogeographical origin on TMCF functioning, and niche conservatism in the evolution of hydraulic traits. The higher drought vulnerability observed in temperate group might be a mechanistic explanation for the restriction of temperate taxa distribution to wetter places during past colder and drier climate. Thus, we suggest hydraulic functional traits may be useful to predict future dynamics of TMCFs under changing climatic conditions. Resumo Florestas nebulares tropicais (TMCF) têm condições climáticas únicas, que permitem a coexistência de linhagens de plantas com diferentes origens fitogeográficas em climas tropicais e temperados. Projeções climáticas futuras sugerem que Florestas Nebulares estarão sujeitas a crescente estresse hídrico, devido a temperaturas mais elevadas e a mudança na zona de ocorrência de neblina, possivelmente levando à mortalidade de árvores e extinções locais e, consequentemente, mudanças na composição e no funcionamento dessas floresta. Caracterizar a composição funcional dessas comunidades, entender os trade‐offs entre atributos e os fatores envolvidos na montagem de comunidades são de extrema importância para melhorar nossa capacidade de prever respostas das comunidades de plantas montanas diante às mudanças climáticas previstas. Neste estudo, nosso objetivo foi testar se espécies de diferentes origens fitogeográficas (ou seja, tropicais ‐ perenes × decíduas ‐ e temperadas) diferem na vulnerabilidade à seca e como a coexistência desses grupos altera a composição hidráulica de TMCFs. Para isso, avaliamos atributos hidráulicos essenciais (dentre eles a resistência do xilema ao embolismo, a margem de segurança hidráulica, controle estômático, ponto de perda de turgor, potencial hídrico mínimo) de 16 espécies dominantes (>70% da área basal da floresta) dentro de uma TMCF, na Mata Atlântica no sudeste do Brasil. Usamos a média ponderada pela comunidade para modelar se a remoção de cada grupo de espécies mudaria a composição funcional hidráulica da comunidade. Grupos temperados, tropicais decíduos e tropicais perenes diferem em seu funcionamento hidráulico e essas diferenças explicam a composição funcional da floresta e a dominância dos táxons. Táxons temperados e tropicais decíduos foram consistentemente mais vulneráveis hidraulicamente (ou seja, margem de segurança mais baixa e menor resistência ao embolismo). A coexistência de diferentes linhagens fitogeográficas é um fator determinante da composição hidráulica de TMCF. Também usamos modelos incluindo filogenia para avaliar a variação de características hidráulicas entre os grupos fitogeográficos, e os resultados sugerem algum conservadorismo de nicho associado ao funcionamento hidráulico das plantas. Nossos resultados fornecem evidência da importância da origem fitogeográfica das espécies no funcionamento de TMCF e do conservadorismo de nicho na evolução das características hidráulicas. A maior vulnerabilidade à seca observada no grupo temperado pode ser uma explicação mecanicista para a distribuição dos táxons temperados se restringir a locais mais úmidos durante o clima mais frio e seco do passado. Assim, sugerimos que as características funcionais hidráulicas podem ser úteis para prever a dinâmica futura de TMCFs sob mudanças nas condições climáticas. A free Plain Language Summary can be found within the Supporting Information of this article. A free Plain Language Summary can be found within the Supporting Information of this article.